2012
DOI: 10.1063/1.3688307
|View full text |Cite
|
Sign up to set email alerts
|

Quasi first-principles Monte Carlo modeling of energy dissipation by low-energy electron beams in multi-walled carbon nanotube materials

Abstract: The energy dissipation pattern of low-energy electron beams (0.3-30 keV) in multi-walled carbon nanotube (MWCNT) materials is studied by Monte Carlo simulation taking into account secondary-electron cascade generation. A quasi first-principles discrete-energy-loss model deduced from a dielectric response function description of electronic excitations in MWCNTs is employed whereby both single-particle and plasmon excitations are included in a unified and self-consistent manner. Our simulations provide practical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
5
1
Order By: Relevance
“…For radiation interactions with GNPs, Geant4-Penelope is unable to precisely reproduce very low-energy electron interactions in the GNP since it is limited to electrons of energies above 100 eV and neglects the reduced dimensionality of the GNPs, this has been shown in work on nanotubes. 31, 43, 44 Furthermore, the interaction probability per Gray with 6 MV photons in this study was found to be higher than that reported in previous studies 9, 18 . We found that this difference was due to the different physics setting used in the two simulations.…”
Section: Discussioncontrasting
confidence: 79%
“…For radiation interactions with GNPs, Geant4-Penelope is unable to precisely reproduce very low-energy electron interactions in the GNP since it is limited to electrons of energies above 100 eV and neglects the reduced dimensionality of the GNPs, this has been shown in work on nanotubes. 31, 43, 44 Furthermore, the interaction probability per Gray with 6 MV photons in this study was found to be higher than that reported in previous studies 9, 18 . We found that this difference was due to the different physics setting used in the two simulations.…”
Section: Discussioncontrasting
confidence: 79%
“…the nanostructure material), which strongly influences mean free paths, energy loss, penetration ranges, etc [40]. Plasmon decay from the NP should also be considered [41] and be included in theoretical studies and Monte Carlo simulations [42].…”
Section: Discussionmentioning
confidence: 99%
“…An approximate scheme has been described elsewhere. 28 However, the details of this procedure are important only for verylow-energy electrons (below $50 eV), and therefore, they are of little practical significance in the present study.…”
Section: B Inelastic Scattering Modelsmentioning
confidence: 99%
“…Recently, the inelastic scattering of low-energy electrons (<30 keV) in CNTs was studied using a dielectric response function determined from experimental optical data and appropriate dispersion relations 25,26 and, along with the original Browning model, 27 was implemented in a homemade MC code to simulate electron transport and energy dissipation in MWCNT materials. 28 The use of a discrete-energy-loss model based on a semi-empirical dielectric response function is presently considered the state-of-the-art for low-energy electron transport in bulk solids and solid surfaces, because it offers a realistic description of the electronic excitations of the material with single-particle and plasmon losses computed self-consistently (under the constraint of sum-rules) within a single model. [29][30][31][32] Furthermore, in place of an undamped plasmon (used in both the UBC 22 and MONSEL 24 codes), more realistic models that account for plasmon dispersion and lifetime broadening can be included.…”
Section: Introductionmentioning
confidence: 99%